2015
DOI: 10.1186/s13041-015-0166-2
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent kinase II and Alzheimer’s disease

Abstract: CaMKII is a remarkably complex protein kinase, known to have a fundamental role in synaptic plasticity and memory formation. Further, CaMKII has also been suggested to be a tau kinase. CaMKII dysregulation may therefore be a modulator of toxicity in Alzheimer’s disease, a dementia characterised by aberrant calcium signalling, synapse and neuronal loss, and impaired memory. Here, we first examine the evidence for CaMKII dysregulation in Alzheimer’s patients and draw parallels to findings in disease models which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 95 publications
(121 reference statements)
8
107
0
1
Order By: Relevance
“…The degree of p(T286)-αCaMKII loss at synaptic locations correlated with severity of the disease [104]. These results suggested that reduction in synaptic CaMKII activity may play an important role in AD pathogenesis [105]. In our experiments we observed direct correlation between reduced nSOC, levels of synaptic p(T286)-αCaMKII and mushroom spine loss in mouse models of AD [23, 24, 26] (Figure 1).…”
Section: Camkii and Can “Tug Of War” And Ad Pathogenesissupporting
confidence: 53%
“…The degree of p(T286)-αCaMKII loss at synaptic locations correlated with severity of the disease [104]. These results suggested that reduction in synaptic CaMKII activity may play an important role in AD pathogenesis [105]. In our experiments we observed direct correlation between reduced nSOC, levels of synaptic p(T286)-αCaMKII and mushroom spine loss in mouse models of AD [23, 24, 26] (Figure 1).…”
Section: Camkii and Can “Tug Of War” And Ad Pathogenesissupporting
confidence: 53%
“…Our current study demonstrates that CaMKII is downstream of NMDAR-dependent synaptotoxicity and suggests that CaMKII inhibition might also prove beneficial as a therapeutic agent for AD (Ghosh and Giese, 2015). However, as in the case of NMDAR, it will be first necessary to develop inhibitors that selectively prevent the oAβ-mediated activation of CaMKII and not the physiological CaMKII activation critical for learning and memory.…”
Section: Discussionmentioning
confidence: 65%
“…The functionality of CAMK2A is measured by the subcellular localization and phosphorylation at Thr286 [63], which were not assessed in this study. However, our previous study demonstrated that in AD the PSD immunoreactivity of the p(Thr286)CAMK2 is shifted away from the dendritic spines as it accumulates at the neuron’s cell body in an Aβ oligomer-dependent phenomenon ([32], reviewed by [59]), and therefore, present results of CAMK2A levels at the PSD could reflect the compartmentalization of this protein.…”
Section: Discussionmentioning
confidence: 91%
“…Calcium/calmodulin-dependent protein kinase type II subunit alpha (CAMK2A) is a serine/threonine protein kinase and is required for hippocampal long-term potentiation (LTP) and spatial learning (as reviewed by [59]). Exposure to A03B2 oligomers decreases the CAMK2 pool at the synapse [60].…”
Section: Discussionmentioning
confidence: 99%